Biosolids at the Farm Gate - Pritchard, Deborah; Penney, N.; Collins, David (Australian Water Association, 2006)
Approximately 15,000 tonnes of dry solids (t DS) of biosolids are spread onto agricultural land throughout Western Australia (WA) annually by a select number of farmers as a substitute to commercial inorganic fertiliser. The costs and management of spreading biosolids are typically perceived as being more difficult and expensive than a conventional fertiliser program. This combined with the added stigma of dealing with a product, which is often controversial, presents the question, "why then do these farmers persist in continuing with their biosolids fertiliser programs"? Very few studies in Australia have examined the cost/benefit to farmers that use biosolids in their farming program and associated factors as to why these farmers continue to want to have biosolids delivered to the farm gate.A survey was therefore conducted on a few key farmers in WA who have routinely used biosolids as part of their farming operations to provide information as to the direct cost comparison between biosolids and commercial fertilisers. All farms surveyed were situated in the 400-450 mm/pa rainfall zone of the northern wheatbelt of WA. The biosolids products investigated included dewatered biosolids cake (DBC) and lime-amended biosolids (LAB). Information was summarised as to the costs for labour and spreading typically associated with either biosolids or commercial fertiliser. The costing structure was based on a 100 ha paddock and took into account such factors as the numbers of person hours worked each day, the number of tractors and loaders and the amount of fuel required for each activity. The costing for biosolids was compared with a traditional inorganic fertiliser program, over a three year period.The average estimated cost to spread and apply biosolids over a 100 ha paddock in a given season was comparative with that of a traditional fertiliser program, being $13,440 and $14,530, respectively. Crop yields were used as a simple indication of the economic value of either biosolids or commercial fertiliser, with some increases to yields of canola in biosolids, but no changes to wheat yields. Given that the cost of spreading biosolids and inorganic fertiliser was similar, the apparent economic benefit of the biosolids was primarily its residual nutrient value in subsequent years. There was no attempt made to analyse changes in the physical, chemical or biological properties of the soil over time.